Chave de identificação dendrológica e síndromes de dispersão de uma área de cerrado sensu stricto, Gurupi, Tocantins - Cândido, Jacqueline Bonfim e (Universidade Federal do Tocantins, 2017)
Tocantins is one of the Brazilian states with the largest area covered by the Cerrado biome, about 72% of native vegetation cover. However, studies with a key to dendrological identification and the phenological behavior associated to the knowledge of the endangered species of Cerrado shrub in the State of Tocantins are still scarce or incipient, thus promoting a lack of technical and scientific information. The establishment of priorities for future conservation strategies and management plans for Cerrado botanical species. In view of the context, the objective was to elaborate a dichotomous key, based on vegetative characteristics of shrub-tree species, in addition to confronting the official lists of endangered Brazilian flora species and to diagnose the dispersal syndromes of the diaspores of a Cerrado Sensu stricto, Gurupi - TO. Five permanent plots of 20×50m, or 1000 m² each, were systematically allocated, 10 m apart. All shrub-arboreal individuals, with circumference at 1.30 m of soil (CAP) greater than or equal to 10 cm were sampled. The botanical materials of the species, when necessary, were herbalised following conventional techniques. The species sampled were classified as the dispersion syndrome and the risk of extinction information found in specialized literature. For the elaboration of the identification key, a selection was made among the 106 species sampled, considering only the species that had absolute density greater or equal to 5 individuals, in this way 54 species were selected, it should be emphasized that this species selection had as objective To include only the species with the greatest recurrence in the cerrado sensu stricto in order to enable the functionality of the key. A total of 106 species, included in 82 genera, belonging to 43 families, were sampled, 61% of which are zoochoric, 31% anemochromic and 8% autochromatic. As for the risk of extinction, 24 are categorized under some degree of risk, according to the red list of CNCFlora, 20 species are Less worrisome, a species almost threatened and another species classified as Insufficient data, according to the IUCN list, a species Is classified as Vulnerable. The identification key based on vegetative characters was composed of 54 shrub-tree species of eudicotiledonias and basal angiosperms, distributed in 47 genera included in 26 botanical families. The preparation of the dendrological identification key was shown to be a functional tool, that is, it allowed a quick and easy identification of the sampled vegetable species.